Reflective groundcovers promote anthocyanin content and advance fruit maturity of ‘Evercrisp’ apples grown in the Mid-Atlantic US - Miah, Md Shipon; Farcuh, Macarena (Frontiers in Plant Science, 2024)
Enhanced skin blush is critical in many apple cultivars to ensure crop profitability and acceptability. Anthocyanin content is a crucial determinant of apple skin blush. Reflective groundcovers are a preharvest management strategy that can improve apple skin blush, but integrative studies assessing its effects at the environmental, physiological, gene, and metabolite levels are lacking. In the present study, we assessed the impact of reflective groundcovers on light environment, preharvest fruit drop, internal ethylene concentration (IEC), fruit-quality-related physicochemical parameters, skin coloration, expression levels of important anthocyanin biosynthesis-related structural genes and transcription factors, and total anthocyanin content of ‘Evercrisp’ fruit located in the canopy’s lower third during on-the-tree ripening, for 2 years, under mid-Atlantic US conditions. Fruit treated with reflective groundcovers displayed an enhanced red skin coloration, reaching >60% blush 1 week before commercial harvest and 2 weeks earlier than control fruit. This resulted from a significantly increased transcript accumulation of anthocyanin biosynthesis-assessed genes, which was promoted by an increased light reflectance (>5–25 times greater than control), which also led to a correspondingly higher total anthocyanin content. Additionally, reflective groundcover-treated ‘Evercrisp’ fruit also exhibited an increased IEC and an advanced maturity, but without differences in fruit drop, as compared to control fruit, during on-the-tree ripening. Reflective groundcovers deployment would allow for an earlier harvest (of at least one week) of ‘Evercrisp’ fruit, which would be packing out in the premium grades as compared to control, thus increasing fruit crop value.